The electroformation and electroreduction of anodic films formed on silver in 0.1 M sodium hydroxide in the potential range of the Ag/Ag2O couple - Lopez Teijelo, Manuel (1984)
The complex electrochemical reactions related to the electroformation and electroreduction of silver(I) oxide films in base electrolyte were investigated by means of combined potentiodynamic techniques and potential steps. The anodic process involves the initial fast OH− ion discharge yielding OH-adsorbed species and later continues to form the silver(I) oxide layer. The latter behaves as a duplex structure anodic layer with a degree of hydration changing with depth. The electroreduction characteristics of the anodic film depend both on potential sweep and anodic charge, and the relationships of the corresponding kinetic parameters fit qualitatively with those predicted by nucleation and growth mechanisms. Activity increases of silver caused by the potential sweeps are interpreted by the simultaneous contribution of the increase in the concentration of silver active surface sites and the change in size distribution of silver electrodeposited from silver(I) oxide.